Appropriate support for national programs; training, research, administration and funding - Markham, R.H.; Sicely, E.M. (1989)
The Biological Control Program (BCP)of the International Institute of Tropical Agriculture and national biological control programs, established specifically to control exotic cassava pests in Africa, are now evolving to address other pest problems. Formal training syllabuses are therefore to be broadened. Equally important is the need for the BCP and national researchers to collaborate to bring the value of biological control to the attention of decision makers. National programs currently need assistance in assessing the impact of the mealybug control campaign. In due course, they should be supported by the BCP in developing their own research programs aligned with national priorities. Within countries, a flexible administrative structure may be needed in which biological control activities are pursued within various institutions, rather than by a single formal program. Internationally, networks may be formed to tackle specific pest problems under the umbrella of a unifying biological control organization. Sustained funding of both national program development and basic research is now needed .National programs may need assistance in preparing projects for funding, but governments must take more responsibility for supporting programs or soliciting the interest of donors.